Colonic diverticulosis as an isolated colonoscopy finding for iFOBT-positive patients - Hordiychuk, Andriy; Ratnayake, Sujith (Eastern Journal of Medical Sciences, 2023)
Colonic diverticular disease is a common medical condition throughout the world. It is one of the most common findings during the endoscopic evaluation of the colon, such as colonoscopy. A retrospective cohort single-centre study was carried out for all patients referred for colonoscopy with positive immunochemical faecal occult blood test (iFOBT) results in 2016-2018, mostly within The National Bower Cancer Screening Program (NBCSP) in QLD, Australia. The cohort of 319 patients were isolated from all iFOBT-positive individuals with such finding as a diverticular disease. Colonic diverticulosis affected the patients above 43 years old with positive iFOBT, more males than females in this study. In most cases, colonoscopy consisted of benign findings, and diverticular disease was revealed in 47.7% of the patients with such indication for colonoscopy as positive iFOBT. 28.8% of the patients were diagnosed with colonic diverticulosis only. The sigmoid colon was affected by diverticulosis in 96.2% of the cases. Overall, the colorectal cancer (CRC) diagnosis rate of 2.7% for the patients in the positive FOBT cohort (Group A) is comparable with other studies. However, the diverticulosis group's CRC rate of 1.6% (Group B) was lower than in available published data.